The Effectiveness of The Inquiry Learning Model on Basic Science Learning Materials on Problem Solving and Critical Thinking Skills - Pujani, Ni Made (Jurnal Pendidikan dan Pengajaran, 2022)
This research study was aimed to improve problem solving and critical thinking skills for science prospective teachers. The study was carried by implementing a Basic Scienc learning tools based on inquiry model for the first semester students of Department of Science Education Universitas Pendidikan Ganesha. The research was employed one group pretest posttest design. The results of the study showed that the inquiry learning model is effective for improving the quality of problem solving skills and effective for improving the quality of critical thinking skills for science prospective teachers.